FORECASTING THE LEADING RISK FACTORS OF EARLY PREGNANCY MISCARRIAGE - Eshmuradova, S.Sh.; Bekbauliyeva, G.N.; Nigmatova , N.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The relevance of the issue cannot be overstated—up to 20% of diagnosed pregnancies end in loss, with 80% of these occurring in the first trimester, before 12 weeks. Objective: The study aimed to investigate biological, socio-hygienic, and medical-organizational risk factors for miscarriage. Materials and Methods: A retrospective study was conducted among women with pregnancy loss at Maternity Complex No. 8 in Tashkent. The first (main) group included 166 women whose last pregnancy ended in spontaneous abortion. The second (control) group consisted of 100 women with a physiological pregnancy course and full-term delivery. Results and Discussion: The analysis identified several key risk factors for spontaneous miscarriage: - Obstetric history: Menarche before age 12 and irregular menstrual cycles, an interpregnancy interval of less than 2 years, a previous spontaneous abortion, fifth or higher-order pregnancy, and late registration with a gynecologist. - Biological factors: Age 35–40 years, short stature, and a high Quetelet index (BMI). - Socio-hygienic factors: Occupation (manual laborers and service workers), low education level, use of particleboard (chipboard) for home interiors, poor diet (lack of meat and fruits), unmarried status, and domestic violence (husband’s physical abuse). When these factors are combined, a woman is classified as being at the highest risk of spontaneous miscarriage.